The effect of plant pesticide Tondxir against the stored product Moth, Ephestia cautella (Walker) (Lepidoptera: Pyralidae) - Swedaan, Samah Sami; Al-Zurfi, Sienaa (Journal of Kerbala for Agricultural Sciences, 2023)
T Many plant extracts could be considered natural, effective methods for controlling insect pests instead of synthetic chemicals. The current examination was designed to assess the mortality percentages of the plant-based pesticide Tondxir on the date moth Ephestia cautella. A series of experiments were carried out in the laboratory to evaluate the pesticide Tondxir's effectiveness in controlling the second and fifth larval stages and the adults of t he date moth. The highest percentage of mortality rates for the second larval stage reached 100% after 5 days at a concentration of 3 ml/liter. However, the mortality rates of the fifth stage and the adult of E. cautella reached 42.14% and 17.50% after two weeks of treatment. A direct relationship was found between the increase in mortality rates with increasing pesticide concentration. The highest percentage of mortality was increased in the fifth larval stage of E. cautella, and they reached 42.14% at the third concentration, compared with the rest of the concentrations. The lowest mortality rate was for the concentration (1ml/liter), as the mortality rate reached (26.07) after 14 days of treatment.